Peak Performance: A Communications-Based Leadership and Teamwork Simulation for Fourth-Year Medical Students. (June 2020) - Smithson, Sarah; Beck Dallaghan, Gary; Crowner, Jason; Derry, Laura Trollinger; Vijayakumar, Akshitha (Ammu); Storrie, Mindy; Daaleman, Timothy P
Background: Medical education has traditionally been rooted in the teaching of health and disease processes, with little attention to the development of teamwork and leadership competencies. Objective: In an era of value-based health care provided by high-functioning teams, new approaches are needed to develop communication, leadership, and teamwork skills for medical students. Design: We designed and piloted a simulation-based educational activity called Peak Performance that linked a workbook, which focused on self-reflection on communication and leadership skills, with professional coaching. The simulation scenario placed students in the role of an upper-level resident on an inpatient service, followed by a small group debrief with students, a clinical faculty member, and a professional executive coach. After the debriefing session, students were invited to complete a self-reflection workbook within 1 week of the initial simulation. The final element of the curriculum was an individualized session with an executive coach. Peak Performance was offered to all fourth-year medical students enrolled in the Social and Health Systems Science required course at the University of North Carolina School of Medicine. Results: Pre-/post-self-assessments of leadership competencies were completed by students. Pre-simulation self-assessment scores ranged from 3.72 to 4.33 on a 5-point scale. The lowest scores were in "Managing Conflict" and "Managing Others." The highest score was in "Self-Awareness." The post-simulation scores decreased in every competency, with "Managing Others" dropping significantly from 3.72 pre-simulation to 3.36 post-simulation (0.31, P < .05). Satisfaction with the curriculum was high, as reflected by a Net Promoter Score of 91% ("excellent" > 50%). Conclusions: A novel simulation-based educational activity linked to professional coaching is a feasible and impactful strategy to develop leadership, communication, and teamwork skills in medical students. Student insight and self-awareness increased as evidenced by a decrease in competency self-assessment after guided reflection and individualized coaching.